2017
DOI: 10.1016/j.cmi.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of withholding antimicrobial treatment in children with cancer, fever and neutropenia, with a demonstrated viral respiratory infection: a randomized clinical trial

Abstract: The reduction of antimicrobials in children with FN and respiratory viral infections, based on clinical and microbiological/molecular diagnostic criteria, should favour the adoption of evidence-based management strategies in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 31 publications
(25 reference statements)
0
21
0
3
Order By: Relevance
“…It is very likely that patients with fever lasting 24-36 h do not need antimicrobial treatment. Santolaya et al have proposed to withhold antimicrobial treatment in children with cancer, fever, and neutropenia if a respiratory infection is present until a result of a polymerase chain reaction microarray for 17 respiratory viruses confirm a viral infection 21 ; in our study, most of the patients had FUO. Some authors have ruled out the importance of the administration time for the first dose of antimicrobial in children with FN 22 .…”
Section: Discussionmentioning
confidence: 49%
“…It is very likely that patients with fever lasting 24-36 h do not need antimicrobial treatment. Santolaya et al have proposed to withhold antimicrobial treatment in children with cancer, fever, and neutropenia if a respiratory infection is present until a result of a polymerase chain reaction microarray for 17 respiratory viruses confirm a viral infection 21 ; in our study, most of the patients had FUO. Some authors have ruled out the importance of the administration time for the first dose of antimicrobial in children with FN 22 .…”
Section: Discussionmentioning
confidence: 49%
“…The misuse of antibiotics in cases of viral respiratory infections is a common problem, and a rapid result for detecting a viral pathogen may prevent the unnecessary use of antibiotics. The rapid diagnosis of respiratory infections also can shorten times in the emergency room, decrease length of stay, or prevent hospitalization and allow improved patient cohorting to prevent nosocomial infections (3,(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Studies investigating outpatient management of pediatric FN have suggested that it is as safe and effective as traditional inpatient therapy, more cost effective, and preferred by patients, parents, and providers, with improvement in quality of life measures . Furthermore, outpatient management greatly reduces the risk of hospital‐acquired infections.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite the high incidence of chemotherapy-induced FN, only a minority of episodes are associated with a serious bacterial infection. [4][5][6][7] Recent investigations have focused on differentiating those patients who will likely develop significant illness from those who will likely have a relatively benign course. 1,5,[7][8][9][10] In adult oncology, there has been substantial research into risk stratification of patients with FN, leading to well-established guidelines for modifications to traditional management.…”
Section: Introductionmentioning
confidence: 99%